1960
DOI: 10.1002/pol.1960.1204414425
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic pressures of aqueous polyvinylpyrrolidone solutions

Abstract: The osmotic pressures of six well‐fractionated samples of polyvinylpyrrolidone were measured in aqueous solution in a Lucite‐block type osmometer. The molecular weights and interaction parameters were determined by employing the theory proposed by Maron for osmotic pressure. It was shown that for all of the fractions, a linear relation existed for ψ and y as predicted by the theory. This new method for expressing osmotic pressure data is compared with the more commonly used expression: It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For infinite diluted solutions, Cerny et al [31] obtained a value of 0.48 (virial expansion truncated at second virial term) using membrane osmometry. Boom et al [9] found in the concentration range of 2.5-30 wt.% a linear dependency of the interaction parameter on the concentration with parameter values between 0.475 (infinite diluted) and 0.63 (30 wt.%) at solution (FH model) using high-pressure membrane osmometry.…”
Section: Reliability Of the Methodsmentioning
confidence: 99%
“…For infinite diluted solutions, Cerny et al [31] obtained a value of 0.48 (virial expansion truncated at second virial term) using membrane osmometry. Boom et al [9] found in the concentration range of 2.5-30 wt.% a linear dependency of the interaction parameter on the concentration with parameter values between 0.475 (infinite diluted) and 0.63 (30 wt.%) at solution (FH model) using high-pressure membrane osmometry.…”
Section: Reliability Of the Methodsmentioning
confidence: 99%
“…The Mark–Houwink constants for HA were obtained from the literature [ 27 ] with values of K = 3.36 × 10 −2 cm 3 /g and a = 0.79 at 25 °C in 0.1 mol/L NaCl. PVP in water had the constants of K = 3.93 × 10 −2 cm 3 /g and a = 0.59 at 30 °C [ 28 ]. All reagents, materials and chemicals used in this study were purchased from POCh (Avantor, Gliwice, Poland) and Chempur (Piekary Slaskie, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…Capillary viscometry was conducted using Ubbelohde‐suspended level instruments with a 0.4‐mm precision bore at T (°C) = 30.00 + 0.02. The conversion of intrinsic viscosity values to viscosity average molecular weights was made using the relationship [η] 30H 2O = 3.93 × 10 −4 M 0.59italicv 10…”
Section: Methodsmentioning
confidence: 99%